Analysis of Green Hydrogen Potential from Biomass Waste in Indonesia: Resource Availability, Energy Potential, and Techno-Economic Feasibility - Eko Gusriadi; Fernando Fernando (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2025)
Indonesia possesses abundant biomass waste resources generated from agricultural, plantation, forestry, and municipal activities, creating significant opportunities for green hydrogen production as part of the transition toward sustainable and low-carbon energy systems. This study aims to analyze the potential of biomass waste as a feedstock for green hydrogen production in Indonesia and evaluate its contribution to national energy security and decarbonization objectives. The research employs a quantitative assessment approach supported by a systematic literature review, utilizing secondary data from government reports, statistical databases, and scientific publications. The methodology includes biomass resource assessment, hydrogen yield estimation, energy potential calculation, environmental impact evaluation, and techno-economic feasibility analysis. The results indicate that Indonesia possesses substantial biomass waste resources, with palm oil residues, rice husks, sugarcane bagasse, coconut shells, forestry residues, and municipal organic waste representing the most significant feedstocks. Among these resources, palm oil biomass demonstrates the highest hydrogen production potential due to its large availability and favorable conversion characteristics. Environmental analysis reveals that biomass-derived hydrogen can reduce landfill dependency, minimize open biomass burning, decrease greenhouse gas emissions, and support circular economy practices through waste valorization. Nevertheless, challenges related to feedstock variability, conversion efficiency, infrastructure limitations, investment costs, and regulatory frameworks remain barriers to large-scale deployment. Overall, the findings demonstrate that biomass waste has considerable potential to support Indonesia’s green hydrogen development, strengthen energy security, promote sustainable waste management, and contribute substantially to national decarbonization and renewable energy transition goals.